Political-Social viewpoints in the Philosophical thought of Xunzi - Van Dung, Vo (Pensando - Revista de Filosofia, 2024)
Xunzi’s sociopolitical views were created during the Spring and Autumn period (Sheng-Hsi, C. 1975). Xunzi’s philosophical thought was born with the aim of transforming society from chaos to prosperity by improving people’s awareness. Xunzi’s views also had certain influences on the social period in which he was living with certain contributions. In this article, the author will focus on clarifying the socio-political views of Xunzi through such issues as identity point of view, views on human nature, and views on society from the perspective of history and philosophy.